Diversity, mechanisms and beneficial features of phosphate-solubilizing Streptomyces in sustainable agriculture: A review - Chouyia, Fatima Ezzahra; Ventorino, Valeria; Pepe, Olimpia (Frontiers in Plant Science, 2022)
Currently, the use of phosphate (P) biofertilizers among many bioformulations has attracted a large amount of interest for sustainable agriculture. By acting as growth promoters, members of the Streptomyces genus can positively interact with plants. Several studies have shown the great potential of this bacterial group in supplementing P in a soluble, plant-available form by several mechanisms. Furthermore, some P-solubilizing Streptomyces (PSS) species are known as plant growth-promoting rhizobacteria that are able to promote plant growth through other means, such as increasing the availability of soil nutrients and producing a wide range of antibiotics, phytohormones, bioactive compounds, and secondary metabolites other than antimicrobial compounds. Therefore, the use of PSS with multiple plant growth-promoting activities as an alternative strategy appears to limit the negative impacts of chemical fertilizers in agricultural practices on environmental and human health, and the potential effects of these PSS on enhancing plant fitness and crop yields have been explored. However, compared with studies on the use of other gram-positive bacteria, studies on the use of Streptomyces as P solubilizers are still lacking, and their results are unclear. Although PSS have been reported as potential bioinoculants in both greenhouse and field experiments, no PSS-based biofertilizers have been commercialized to date. In this regard, this review provides an overview mainly of the P solubilization activity of Streptomyces species, including their use as P biofertilizers in competitive agronomic practices and the mechanisms through which they release P by solubilization/mineralization, for both increasing P use efficiency in the soil and plant growth. This review further highlights and discusses the beneficial association of PSS with plants in detail with the latest developments and research to expand the knowledge concerning the use of PSS as P biofertilizers for field applications by exploiting their numerous advantages in improving crop production to meet global food demands.